Influence of Atmospheric Turbulence Channel on a Super-Resolution Ghost Imaging Transmission System Based on Plasmonic Structure Illumination Microscopy - Wang, Kaimin; Wang, Zhaorui; Bai, Chunyan; Zhang, Leihong; Dai, Bo; Zhang, Yuxing; Ye, Hualong; Zhang, Zhisheng; Han, Xiaoxuan; Xue, Tong; Xu, Meiyong; Hu, Jiafeng; et al. (Frontiers in Physics, 2020)
Ghost imaging is a research focus of image area with various advantages against traditional imagings. However, most of the existing works didn’t have a better resolution than the diffraction limit. In this work, we presented a ghost imaging system with plasmonic structure illumination microscopy (PSIM), to achieve super-resolution imaging. The resolution can reach 3 to 4 times of diffraction limit with surface plasmon polaritons (SPPs) and structure illumination microscopy (SIM) theory. In addition, imaging results are obtained accordingly. This method has great research value in medical fields such as micro-imaging and endoscope. Then, we used the gamma-gamma intensity-fluctuation model to simulate the ghost imaging system in atmospheric turbulence channel. By setting proper values of the parameters such as transmission distance and refractive-index structure parameter, the peak signal-to-noise ratio (PSNR) performance and symbol-error rate (SER) performance are obtained to evaluate the imaging quality, which provides a theoretical model to further research the ghost-imaging algorithm.